Perancangan UI/UX Aplikasi Tanda Bahaya untuk Perlindungan Anak “SafeKid” Berbasis Mobile - Christirahma, Ratri Desy; Karyawati, Anak Agung Istri Ngurah Eka (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 4 (2023): JNATIA Vol. 1, No. 4, Agustus 2023DO - 10.24843/JNATIA.2023.v01.i04.p05, 2023)
During the last 36 years, the National Center For Missing and Exploited Children has received more than 5 million calls about cases of missing children. In 2019 alone, the NCMEC assisted law enforcement and families with more than 29,000 cases of missing children. In Asia itself, it is estimated that there are around 20,000 to 200,000 missing children. More precisely in China and Southeast Asia. To help reduce the rate of loss of children in Indonesia, the authors created a design solution using the prototyping and UML methods. By using this prototype, users will be able to track the child's location and provide assistance in the form of a help button if something happens to the child. With this solution, it is hoped that it can help children who are in an emergency and parents who have lost their children so as to suppress the growth of cases of missing children.